Validation of the French version of COHIP-SF-19 among 12-years children in New Caledonia - Amal Skandrani; Nada El Osta; Hélène Pichot; Caroline Eschevins; Bruno Pereira; Stéphanie Tubert-Jeannin (BMC, 2022)
Abstract Background Assessment of oral health-related quality of life is now associated to clinical indicators in epidemiological studies. This study aimed at validating the French Short Form of the Child Oral Health Impact Profile (COHIP-SF-19) and assessing the impacts of oral diseases among schoolchildren in New Caledonia (NC). Methods A sample of 12-years-old children (n = 971) was selected in 2019 in NC using a random, stratified, and clustered sampling technique. Children filled the French COHIP-SF-19 questionnaire. Information on sociodemographic characteristics, oral hygiene habits, perception of oral health problems were also collected through self-administered questionnaires or from the schools' database. Dental status (dental caries, gingival status, and dental functional units) was clinically recorded at school by four calibrated examiners. Cronbach's alpha and intraclass correlation coefficients (ICC) were calculated. Kruskal-Wallis tests and spearman correlations were used along with multilevel mixed models taking into account the cluster and examiner effects. A confirmatory factor analysis was conducted and sensitivity analyses were performed. Results Among the 693 children examined, 557 children were included. Oral diseases were frequent in the study population 40% had dental caries and 55% presented gingivitis. The COHIP scores ranged from 7 to 76 (57.9 ± 9.96) with 96.4% of the children having experienced oral health problems, 81.7% reporting functional impacts and 90.5% socio-emotional impacts. Overall, the French COHIP-SF-19 showed satisfactory psychometric characteristics. Internal consistency was high (Cronbach's alpha = 0.80) and reproducibility excellent (ICC = 0.9). Discriminant and concurrent validity were adequate. Indeed, children with less optimal social situation, impaired dental status, declaring severe dental problems or difficulties in accessing oral health care showed lower COHIP-SF-19 scores. Factor analyses suggested a four-component structure with identification of a new domain (self -image) and changes in the repartition of the items within the original domains. Sensitivity analyses showed similar results for children with partial or complete answers in the COHIP questionnaire. Conclusions The French COHIP-SF-19 showed satisfactory psychometric characteristics and allowed to identify the high impacts of oral diseases in New Caledonian children, namely for socially deprived children.